Kurikulum Berbasis Nilai Cinta: Rekonstruksi Ontologis dan Aksiologis Pendidikan Madrasah - Sandi Ferdy Yulianto; Mohammad Iqbal Falahy; Nur Ahid (Kariman: Jurnal Pendidikan Keislaman, 2026)
This study aims to reconstruct the essence of the madrasah curriculum from ontological and axiological perspectives by positioning the value of love as the fundamental orientation in the process of internalizing educational values. The research problem stems from the tendency to interpret the curriculum in a manner that remains administrative and focused on cognitive aspects, resulting in the affective and spiritual dimensions not yet being systematically integrated into the curriculum structure. This study employs a qualitative approach with a library research design. Research data are sourced from primary and secondary literature, including works on the philosophy of education, curriculum theory, and classical and contemporary Islamic educational studies relevant to the concepts of educational values and objectives. Data collection was conducted through literature documentation, while data analysis employed content analysis and philosophical analysis to identify the curriculum’s ontological structure and its underlying axiological orientation. The research findings indicate that the madrasah curriculum must be understood as a normative and existential entity that not only regulates instructional content but also shapes students’ educational experiences and value orientations. Axiological reconstruction positions the value of love as an ethical principle that frames educational goals, curriculum content, learning strategies, and the institutional culture of the madrasah. This study formulates a Three-Dimensional Integration Model of Love-Based Madrasah Curriculum, consisting of structural, pedagogical, and cultural dimensions that operate systemically as a framework for value internalization. These findings contribute to the development of Islamic curriculum philosophy by emphasizing the importance of integrating the value of love into curriculum design to build a madrasah education that is humanistic, transcendental, and oriented toward character formation.